2008
DOI: 10.2169/internalmedicine.47.1219
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nicotine Dependence Level and Community-Acquired Pneumonia in Young Soldiers: A Case Control Study

Abstract: Objective Smoking is an important risk factor in the development of community-acquired pneumonia (CAP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…All except two studies included both genders; two studies only included men. [15,16] Five studies had selected clinical populations including patients with human immunodeficiency virus (HIV)[17], selected HIV-related medical conditions[16], minor thoracic injury[18] and chronic obstructive pulmonary disease (COPD)[19,20]. One study reported an outbreak of Legionnaires’ disease and included participants who visited an aquarium.…”
Section: Resultsmentioning
confidence: 99%
“…All except two studies included both genders; two studies only included men. [15,16] Five studies had selected clinical populations including patients with human immunodeficiency virus (HIV)[17], selected HIV-related medical conditions[16], minor thoracic injury[18] and chronic obstructive pulmonary disease (COPD)[19,20]. One study reported an outbreak of Legionnaires’ disease and included participants who visited an aquarium.…”
Section: Resultsmentioning
confidence: 99%
“…Direct evidence of a role for tobacco in the development of heat illness is lacking, but smoking-associated risks that could precipitate or contribute to an episode in military personnel include decreased physical fitness26 27 and intercurrent illness 1928 29 It is disappointing that the requirement to achieve significant reductions in smoking among British Army personnel23 25 is yet to be met in the training environment and a fresh approach to prevention may be required. In contrast, the use of dietary and exercise supplements was much lower than reported for UK military personnel deployed on operations to Afghanistan in 2010 (40.2%)24 and Iraq in 2009 (32.0%)30 and for British Army personnel attending UK-based training establishments in 2010/2011 (38%) 14.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is also an important risk factor in the development of community acquired pneumonia. Infection incidence increases in smokers due to impaired mucociliary clearance, increased inflammation and adherence of pathogens, epithelial destruction and changes in the host defense mechanisms (Tas et al, 2008).…”
Section: Risk Factors Of Respiratory Diseases In the Military Environmentioning
confidence: 99%